Comparisons between lower-extremity strengthening exercises and foot orthoses for improving medial longitudinal arch height in individuals with ﬂexible ﬂat foot: an 8-week randomised clinical trial - Engkananuwat, Phoomchai; Kanlayanaphotporn, Rotsalai (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. Flexible ﬂatfoot is a recognised risk factor for lower extremity injuries. This study aimed to compare changes in the medial longitudinal arch (MLA) between a strengthening exercise group (EG) and a foot orthoses group (FOG).Methods. Thirty-eight healthy participants with bilateral ﬂexible ﬂatfoot were randomly assigned to either the EG or the FOG (n = 19 per group). The EG performed exercises 5 days a week, while the FOG wore foot orthoses for more than ﬁve hours daily. Measurements of navicular drop, arch height index (AHI), plantar pressure, static balance, dynamic balance, and lower extremity muscle strength were taken at baseline, 4 weeks, and 8 weeks.Results. Both groups signiﬁcantly improved in most measures at 4 and 8 weeks compared to baseline. At 8 weeks, the EG demonstrated substantially greater improvements in navicular drop (p < 0.001, d = 1.542) and AHI (p < 0.001, d = –1.286) than the FOG. The EG also exhibited signiﬁcantly better improvements than the FOG in static balance in the anteroposterior direc-tion (p = 0.027, d = 0.517), dynamic balance in the medial (p = 0.049, d = –0.460) and lateral directions (p = 0.017, d = –0.562), and lower extremity muscle strength (p < 0.05, d = –0.755 and –1.109, r = 0.473).Conclusions. Lower-extremity exercise proved more eﬀective than foot orthoses in enhancing the MLA and improving balance in individuals with ﬂexible ﬂatfoot.
Keywords: exercise; ﬂexible ﬂatfoot; foot orthoses; medial longitudinal arch; navicular drop